1996
DOI: 10.1111/j.1365-2249.1996.tb08290.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of estradiol benzoate on development of collagen-induced arthritis (CIA) in the Lewis rat are mediated via suppression of the humoral response against denatured collagen type II (CII)

Abstract: SUMMARYThe effects of estradiol benzoate (EB) on the development of anti-CII antibodies and their pathogenic potential were studied during the progress of established CIA in the rat. CIA was induced in mature female Lewis rats by two subcutaneous inoculations containing bovine native CII (BCIIn), emulsified in Freund's incomplete adjuvant. Clinical arthritis fully developed by day 18 and then EB (1 mg/kg body wt per day, diluted in corn oil (CO)) was administered intramuscularly every second day thereafter. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Apparently, ET is able to suppress the overall initial immune responses sufficiently to prevent one-third of the animals from ever developing visual signs of disease, while not ruling out some level of immune response. Oestradiol treatment has also been shown to decrease the production of specific IgG2a anti-collagen type II antibodies and alter the T helper (Th) profile of the autoimmune T cell response towards a poor antibody isotype [33,34]. In addition, the direct effects of oestrogens on articular cartilage health have been proposed recently, and preliminary evidence has been provided [12].…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, ET is able to suppress the overall initial immune responses sufficiently to prevent one-third of the animals from ever developing visual signs of disease, while not ruling out some level of immune response. Oestradiol treatment has also been shown to decrease the production of specific IgG2a anti-collagen type II antibodies and alter the T helper (Th) profile of the autoimmune T cell response towards a poor antibody isotype [33,34]. In addition, the direct effects of oestrogens on articular cartilage health have been proposed recently, and preliminary evidence has been provided [12].…”
Section: Discussionmentioning
confidence: 99%
“…GEO was dosed at 28 mg/kg/d in order to: 1) facilitate comparison with the in vivo potency of isolated gingerols, which were dosed at 25 mg/kg/d [6], and to 2) approximate the GEO dose received by rats treated with the crude ginger extract in prior experiments (containing approximately 32 mg/kg/d GEO [and 25 mg/kg/d gingerols]) [6]. In separate experiments, in order to compare the anti-inflammatory effects of GEO to those of estrogen, rats were treated beginning 4 days prior to SCW injection with 17-β estradiol (E 2 , Sigma, St. Louis, MO) using pharmacologic doses with demonstrated anti-arthritic efficacy in other rat arthritis models [20-22] that also normalize bone parameters and prevent uterine atrophy in ovariectomized rats [23]25] (200 μg/kg or 600 μg/kg subcutaneously five times a week, as indicated, vs. vehicle alone [1 μl/g sesame oil]). Joint inflammation was determined in a blinded fashion by daily assessment of arthritic index (AI) in each distal limb using standard criteria (0 = normal; 1 = slight erythema and edema; 2 = increased edema with loss of landmarks; 3 = marked edema; 4 = marked edema with ankylosis on flexion) [19,20,23,24].…”
Section: Methodsmentioning
confidence: 99%
“…Waksman and co-workers [32] showed that in mature female Lewis rats clinical arthritis fully developed by day 18 after two subcutaneous inoculations of CII emulsified in IFA. In our investigations, the severest CIA among female animals developed in the 3rd group of Lewis rats given one injection of CII + IFA + MDP, and polyarthritis in 20% of animals on day 12 after immunization was observed.…”
Section: Discussionmentioning
confidence: 99%